In Vitro Antimicrobial Activity of Ceftizoxime Against Glucose-Nonfermentative Gram-Negative Rods - Yabuuchi, Eiko (1981)
Ceftizoxime, a new cephalosporin, was active against Pseudomonas cepacia, Flavobacterium meningosepticum, Alcaligenes faecalis, and Acinetobacter calcoaceticus and was more potent against Pseudomonas aeruginosa and Pseudomonas putida than was carbenicillin.